Impact of a classroom standing desk intervention on daily objectively measured sedentary behavior and physical activity in youth. Issue 9 (September 2018) - Silva, Danilo R.; Minderico, Cláudia S.; Pinto, Fernando; Collings, Paul J.; Cyrino, Edilson S.; Sardinha, Luís B.
Abstract: Objectives: We investigated the impact of a standing desk intervention on daily objectively monitored sedentary behavior and physical activity in 6th grade school students. Design: Cluster non-randomised controlled trial. Method: Two classes (intervention students: n = 22 [aged 11.8 ± 0.4 years]; control students: n = 27 [11.6 ± 0.5 years]) from a public school in Lisbon were selected. The intervention involved replacing traditional seated classroom desks for standing desks, for a total duration of 16 weeks, in addition to performing teacher training and holding education/motivation sessions with students and parents. Sedentary behavior (ActivPAL inclinometer) and physical activity (Actigraph GT3X+ accelerometer) were measured for seven days immediately before and after the intervention. Results: There were no differences in baseline behaviors between intervention and control groups ( p > 0.05). At follow-up (16 weeks), it was observed that the intervention group had decreased time spent sitting (total week: −6.8% and at school: −13.0% relative to baseline) and increased standing (total week: 16.5% and at school: 31.0%) based on inclinometer values (p-value for interaction group*time <0.05). No significant differences in activity outcomes were observed outside school time (week or weekend) between groups. Conclusion: We conclude that a 16 week classroom standing desk intervention successfully reduced sitting time and increase standing time at school, with no observed compensatory effects outside of school time.